V-019 LAPAROSCOPIC CONTROL OF HEMOPERITONEUM AFTER TACKER FIXATION IN TAPP HERNIA REPAIR. (13th October 2022) - Ramirez, A; Bascuas, B; Delgado, M; Licardie, E; Guadalajara, J
Abstract: Aim: The use of tackers for peritoneal closure in TAPP (transabdominal preperitoneal approach) is controversial because of the associated risk of vasculo-nerve injury. We present the case of a 56 years old male who came for hypovolemic shock due to hemoperitoneum after TAPP hernia repair in another center 72 hours earlier. Material & Methods: We opted for an exploratory laparoscopy showing a massive hemoperitoneum due to a bleeding from the left epigastric artery at the site of placement of a tacker. Hemostasis was performed with bipolar energy and peritoneal approximation with glue after washing and aspiration. Results: The patient was discharged on the third day without any complications. Conclusions: Peritoneal flap closure in TAPP remains a controversial issue despite finding no significant differences between the different closure methods in the literature. Blind placement may injure vessels and nerves that require subsequent urgent surgery. In selected patients, if the patient is stable, laparoscopy through the same trocars is a safe and reliable option to resolve hemoperitoneum after epigastric artery injury.